Selective hydrogenolysis of glycerol to 1,2-propanediol: comparison of batch and continuous process operations - Rode, Chandrashekhar V; Ghalwadkar, Ajay A.; Mane, R. B.; Hengne, Amol M.; Jadkar, Sachin T.; Biradar, Narayan S. (Organic Process Research & Development, 2010)
The screening of copper chromite catalysts with various promoters such as Al, Zn, and Ba for glycerol hydrogenolysis to 1,2-propanediol (1,2-PDO) in a batch reaction showed that Cu-Cr (Ba) catalyst gave the highest conversion of 34% and selectivity of 84% to 1,2-PDO. In a continuous operation (23 g catalyst bed) the same catalyst showed higher conversion of glycerol and selectivity for 1,2-PDO of 65% and > 90%, respectively, with an on-stream activity of similar to 800 h. Better performance in a continuous operation could be due to the in situ activation of the catalyst, suppression of glycerol cracking to ethylene glycol, as well as excessive hydrogenation of 1,2-PDO to 2-propanol due to lower contact time of 1.3 h as compared to that in a batch operation (5 h). Effects of various process parameters on conversion and selectivity also have been compared for batch and continuous operations.

Surface species of supported ruthenium catalysts in selective hydrogenation of levulinic esters for bio-refinery application - Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Catalysis Letters, 2012)
Several supported noble metal catalysts were screened for the hydrogenation of methyl levulinate to gamma-valerolactone (GVL). Among these catalysts 5 % Ru/C showed the highest conversion of 95 % of methyl levulinate with 91 % selectivity to GVL. A detailed characterization was carried out using TPR, XRD, XPS and BET techniques. XPS studies revealed that higher extent of Ru-0 species in case of carbon supported Ru was responsible for its higher hydrogenation activity as compared to Ru on other supports. Effect of process parameters such as temperature, H-2 pressure, catalyst and substrate concentration and metal loading on methyl LA conversion and selectivity to GVL also has been studied. 5 % Ru/C catalyst was found to be stable up to five reuses.
Keywords: 5 % Ru/C; Biofeedstock; gamma-Valerolactone; H-2-TPR; Hydrogenation; Methyl levulinate; XPS

Single pot conversion of furfuryl alcohol to levulinic esters and gamma-valerolactone in the presence of sulfonic acid functionalized ILs and metal catalysts - Hengne, Amol M.; Kamble, Sumit B.; Rode, Chandrashekhar V. (Green Chemistry, 2013)
Ionic liquids functionalized with acidic anions, HSO4, ClSO3H, PTSA, TFA (MIm), HSO4 and TFA (NMP) were found to efficiently (99% conversion) catalyze the alcoholysis of furfuryl alcohol (FAL) in the presence of methanol, ethanol, n-butanol and isopropyl alcohol (IPA) to the corresponding levulinic acid esters under mild temperature (90-130 degrees C) conditions. The extended alkyl chain length of [MIm] using 1,4-butane sultone enhanced the Bronsted acidity of [BMIm-SH][HSO4] catalyst resulting into the highest selectivity of >95% to Me-LA. An increase in both temperature and catalyst concentration increased the furfuryl alcohol conversion and selectivity to levulinate esters. In contrast, an increase in the substrate concentration from 5 to 15% caused a decrease in Me-LA selectivity due to accumulation of intermediate ethers of furfuryl alcohol. Using a combination of [BMIm-SH][HSO4] and 5% Ru/C catalyst, direct conversion of FAL to gamma-valerolactone (GVL) is shown for the first time. A complete conversion of FAL with the highest selectivity of 68% to GVL could be achieved under optimum conditions while higher Ru loading enhanced the GVL selectivity to 94% in the hydrogenation step of this tandem approach. Our catalyst system could be efficiently recycled five times retaining the original activity and selectivity levels.

Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Surface synergism of an Ag-Ni/ZrO2 nanocomposite for the catalytic transfer hydrogenation of bio-derived platform molecules - Hengne, Amol M.; Malawadkar, Atul V.; Biradar, Narayan S.; Rode, Chandrashekhar V. (RSC Advances, 2014)
Levulinic acid was completely and selectively converted to GVL, in the presence of formic acid over an Ag-Ni/ZrO2 catalyst. The synergism between Ag and Ni in transfer hydrogenation eliminates the need for external hydrogen, making the process safer. The magnetic nature of the catalyst offers easy recovery for efficient recycling. This approach is standardized for the hydrogenation of several C-3-C-6 platform molecules in an aqueous medium.

Single pot transfer hydrogenation and aldolization of furfural over metal oxide catalysts - Biradar, Narayan S.; Hengne, Amol M.; Sakate, S. S.; Swami, R. K.; Rode, Chandrashekhar V. (Catalysis Letters, 2016)
One pot catalytic transfer hydrogenation (CTH) of furfural to furfuryl alcohol (FAL) by using hydrogen producing alcohols and simultaneous aldolization of carbonyl compounds produced during CTH, with furfural was achieved over non-noble metal oxides with bifunctional sites. Basic sites of MgO responsible for abstraction of proton showed complete conversion of furfural to give FAL and C8 monomer in a ratio of 3:1, respectively, the later altered to 1:1 by incorporating Al into MgO. Catalyst stability was established by its four cycles study. [GRAPHICS]
Keywords: Aldol; furfural; Furfuryl alcohol; Metal oxides; transfer hydrogenation

Single pot selective hydrogenation of furfural to 2-methylfuran over carbon supported iridium catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K-W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Green Chemistry, 2018)
Various iridium supported carbon catalysts were prepared and screened for the direct hydrogenation of furfural (FFR) to 2-methyl furan (2-MF). Amongst these, 5% Ir/C showed excellent results with complete FFR conversion and highest selectivity of 95% to 2-MF at a very low H-2 pressure of 100 psig. Metallic (Ir degrees) and oxide (IrO2) phases of Ir catalyzed the first step hydrogenation involving FFR to FAL and subsequent hydrogenation to 2-MF, respectively. This was confirmed by XPS analysis and some control experiments. At a low temperature of 140 degrees C, almost equal selectivities of FAL (42%) and 2-MF (43%) were observed, while the higher temperature (220 degrees C) favored selective hydrodeoxygenation. At optimized temperature, 2-MF was formed selectively while higher pressure and higher catalyst loading favored ring hydrogenation of furfural rather than side chain hydrogenation. With the combination of several control experimental results and detailed catalyst characterization, a plausible reaction pathway has been proposed for the selective formation of 2-MF. The selectivity to various other products in FFR hydrogenation can be manipulated by tailoring the reaction conditions over the same catalyst.